High Resistance to β-Lactams but Sustained Susceptibility to Colistin and Carbapenems in Escherichia coli Isolated from Urinary Tract Infections - Mohammed, Lalan Rebaz; Hama Soor, Taib Ahmed (Kurdistan Journal of Applied Research, 2025)
Multidrug-resistant bacterial strains represent a growing public health threat, particularly in clinical environments, as they significantly impair the success of treatment and control strategies for infectious diseases. This cross-sectional study investigated the antimicrobial resistance profiles of 100 Escherichia coli (E. coli) isolates derived from urine specimens of patients with symptomatic urinary tract infections (UTIs) in Sulaymaniyah City, Iraq. The samples were obtained from individuals visiting both public and private hospitals between November 2024 and February 2025. Bacterial identification and antimicrobial susceptibility testing were conducted using the VITEK 2 automated system at hospital laboratories, and molecular confirmation of the isolates was achieved through amplification of the uidA (glucuronidase) gene specific to E. coli. A total of ten antibiotics from various antimicrobial classes were tested. Colistin demonstrated complete effectiveness, with a 100% susceptibility rate, followed by doripenem (93%), imipenem (84%), tigecycline (71%), and amoxicillin-sulbactam (65%). In contrast, amoxicillin and amoxicillin-clavulanate showed high resistance rates of 83% and 82%, respectively. Resistance to cephalosporins was also considerable, with cefixime and ceftazidime exhibiting resistance rates of 70% and 60%. The findings highlight the continued effectiveness of colistin and carbapenems but draw attention to the concerning resistance to widely used β-lactams and cephalosporins. These results underscore the necessity of sustained antimicrobial resistance surveillance and improved antibiotic stewardship. The data generated in this study are critical for guiding empirical treatment decisions and enhancing the clinical management of E. coli-associated UTIs in the region.